(untitled) (Intercom - Brazilian Journal of Communication Sciences, 2024)
The objective of this paper is to present the theories related to hybrid warfare, methodologically defining the deterrence operations commonly used in semiotic conflicts. Through an interdisciplinary bibliographical review, it is intended to elaborate the context of communication, as well as information, in which we find ourselves today, when digital platforms, the means of almost everything, omnipotently dominate the social and political organizations of nations. It is expected, therefore, to provide a framework for analyzing the dynamics of networks as part of a political conflict on a global scale.